Estudo da estabilidade e propriedades de clusters atômicos por métodos ab initio de alto nível - Mateus Xavier Silva (2018)
At the nanoscale the properties of an atomic or molecular aggregate depend largely on its size, changing in a non-uniform pattern as the system increases. Given that these properties are distinct from the bulk matter, new types of materials with different applicability may be found. Specific focus is given to metallic clusters, often with potential application in catalysis, and to atomic nitrogen clusters, which have been lately calling the attention of the scientific community for being goodcandidates for high energy density materials. There is a rising interest nowadays in employing nanoscale materials as new possible types of fuels. To be considered an efficient fuel, the candidate material must be sufficiently unstable in order to react with another system and then release a considerable amount of energy. On the other hand, it must be stable enough to be synthesized and stored without spontaneously decomposing itself. To accomplish the goal of being considered greenthese materials must not only generate reasonably less toxic products than the current widely spread fuels do, but also demonstrate higher performances while being technically as well as economically attractive. In this context, polynitrogen systems have been studied due to their dissociation into inert N2 molecules that may release huge amounts of energy. The normal approach taken in the study of clusters is to first use an empirical analytic potential, such as to have a fast way of evaluating the energy, and explore it using global optimization methods such as genetic algorithms. Such empirical potentials often turn out to be a poor representation of the system, especially in the few atoms regime,since they cannot reproduce quantum effects. Therefore, a genetic algorithm coupled to electronic structure calculations was developed for searching, in the first instance, the global minimum in the ab initio potential energy landscape of alloy clusters. This allows a non-biased search over new structures that could not be unraveled by empirical potentials. The convergence criterion for the energy gradient in local optimization is progressively reduced over the generations in order to require less energy evaluations. A case studied is the Na-K alloy with MP2/ECP energies, where it is demonstrated that the algorithm is efficient in obtaining global minima. Particular analysis of a 2D-3D-2D transition in the 6-atoms case is studied in detail for the first time. Completely new structures are unveiled for larger alloy clusters. Subsequently, this quantum genetic algorithm was upgraded and employed to survey the DFT potential energy hypersurfaces of closed-shell atomic nitrogen clusters up to ten atoms. An atom-atom distance threshold parameter, controlled by the user, and an operator manager were added to the standard evolutionary procedure. Both B3LYP and PBE exchange-correlation functionals with 6-31G basis set were explored using the algorithm. Further evaluation of the structures generated was performed through reoptimization and vibrational analysis within MP2 and CCSD(T) levels employing larger correlation consistent basis set. The binding energies of all stable polynitrogen structures found were calculated and compared, as well as their energies relative to the dissociation into N2, N3+ and N3- molecules. With the present approach we confirmed some previously reported polynitrogen structures and predicted the stability of new ones. We can also conclude that theenergy surface profile clearly depends on the calculation method employed. Theoretical investigations of the electronic potential energy curves associated with the dissociation of the N4 (Td) into two N2molecules were also performed for the electronic ground state and the first excited states using CASSCF(12,12) level of theory. The graphs containing the dissociation paths studied involved singlet and triplet states, where it was possible to observe both conical intersections and intersystem crossings. Possible alternative dissociation channels for the N4 (Td) were then inferred from these crossings and photoexcitation of this species. Insights were also provided to unravel a possible reaction mechanism involving the abstraction of a nitrogen atom from a N2 molecule in an excited electronic state, by another excited N2 molecule, to produce linear N3.